Preoperative albumin/globulin ratio is a potential prognosis predicting biomarker in patients with resectable gastric cancer - Xue, Fan; Lin, Feng; Yin, Min; Feng, Ning; Zhang, Xu; Cui, You-Gang; Yi, Yu-Peng; Kong, Xiang-Yu; Chen, Xi; Liu, Wen-Zhi (Turkish Journal of Gastroenterology, 2017)
Abstract Background/Aims: To investigate the prognostic significance of preoperative albumin to globulin ratio (AGR) in patients with resectable gastric cancer (GC). Materials and Methods: According to the inclusion criteria, 269 GC patients (male:female=127:67; median age: 67 years) with a stage I through III who underwent gastrectomy with D2 lymphadenectomy and R0 resection were included. These patients were categorized into two groups, namely low AGR group and high AGR group, based on a cutoff point that was obtained using a receiver-operating characteristic curve. The correlations of preoperative AGR with the clinicopathological characteristics and overall survival were analyzed. Univariate and multivariate analysis were performed to assess the prognostic value of preoperative AGR. Results: Age, gender, tumor size, T stage, and preoperative hemoglobin were significantly different between the low and high AGR groups (p Conclusion: Preoperative AGR was significantly associated with the prognosis of GC patients in our study. In addition, preoperative AGR is suggested to be a simple but efficient prognosis predicting biomarker in patients with GC. Cite this article as: Xue F, Lin F, Yin M, et al. Preoperative albumin/globulin ratio is a potential prognosis predicting biomarker in patients with resectable gastric cancer. Turk J Gastroenterol 2017; 28: 439-45.